2016
DOI: 10.1128/jvi.01091-16
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Epidemic Diarrhea Virus Infection Inhibits Interferon Signaling by Targeted Degradation of STAT1

Abstract: Porcine epidemic diarrhea virus (PEDV) is a worldwide-distributed alphacoronavirus, but the pathogenesis of PEDV infection is not fully characterized. During virus infection, type I interferon (IFN) is a key mediator of innate antiviral responses. Most coronaviruses develop some strategy for at least partially circumventing the IFN response by limiting the production of IFN and by delaying the activation of the IFN response. However, the molecular mechanisms by which PEDV antagonizes the antiviral effects of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 80 publications
(98 reference statements)
1
59
2
Order By: Relevance
“…Among them, STAT1 and STAT2 are the most important in the IFN signaling pathway [23]. In vitro studies have demonstrated that PEDV infection inhibited the interferon signaling by targeted degradation of STAT1 [20,32]. However, in this work, no significant change was found in STAT1 and STAT2 in the two PEDV infected groups.…”
Section: Discussionmentioning
confidence: 61%
“…Among them, STAT1 and STAT2 are the most important in the IFN signaling pathway [23]. In vitro studies have demonstrated that PEDV infection inhibited the interferon signaling by targeted degradation of STAT1 [20,32]. However, in this work, no significant change was found in STAT1 and STAT2 in the two PEDV infected groups.…”
Section: Discussionmentioning
confidence: 61%
“…Vero E6 (African green monkey kidney epithelial cells), IPEC-J2 (porcine intestinal epithelial cell clone J2), and BHK (baby hamster kidney fibroblasts) cell lines were grown and maintained in Dulbecco minimum essential medium (DMEM) supplemented with 10% heatinactivated fetal bovine serum (FBS; Thermo Fisher) (58). All cells were cultured in a humidified atmosphere at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…An immunofluorescence assay was performed as previously described (58). Briefly, Vero E6 and IPEC-J2 cell monolayers were inoculated with PEDV at MOIs of 0.1 and 1, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It is generally believed that the type I (IFNα, IFN-β) and type III IFNs (IFN-λ2, IFN-λ3) play essential roles in antiviral defense [11]. Many viruses, including coronaviruses, have evolved strategies to counteract the signaling cascades of the innate immune system, especially through inhibiting IFN signaling and reduction of IFN production [12]. Viral proteins from different viruses, including influenza virus [13], Herpes virus [14], Coronaviruses severe acute respiratory syndrome (SARS) [15], Middle east respiratory syndrome (MERS) [16] and PEDV [17] have been identified as IFN antagonists.…”
Section: Introductionmentioning
confidence: 99%